The UNHCR and the supervision of international refugee law / edited by James C. Simeon. - Simeon, James C. (Cambridge University Press, 2013)
The 1951 Convention relating to the Status of Refugees, and its 1967 Protocol, and many other important international instruments recognize the unique role the UNHCR plays in protecting refugees and supervising international refugee law. This in-depth analysis of the UNHCR's supervisory role in the international refugee protection regime examines the part played by key institutions, organizations and actors in the supervision of international refugee law. It provides suggestions and recommendations on how the UNHCR's supervisory role can be strengthened to ensure greater State Parties' compliance to their obligations under these international refugee rights treaties, and contributes to enhancing the international protection of refugees and to the promotion of a democratic global governance of the international refugee protection regime.